2015
DOI: 10.1097/mao.0000000000000610
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Vestibulo-Ocular Reflex Function

Abstract: Objective To determine age-related changes in vestibulo-ocular reflex (VOR) function in community-dwelling adults, and evaluate these for associations with demographic characteristics and cardiovascular risk factors. Study Design Cross-sectional analysis within the Baltimore Longitudinal Study of Aging (BLSA), a longitudinal prospective cohort study. Setting Vestibular testing laboratory within an acute care teaching hospital. Patients Community-dwelling adults enrolled in the BLSA. Intervention(s) Hor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 96 publications
(48 citation statements)
references
References 33 publications
1
45
0
2
Order By: Relevance
“…Notably, this decline was not associated with any symptoms or signs of disequilibrium (47). By contrast, the patients, whose VOR responses were depressed at the start of testing, did not show any significant decline (48). Carol et al analyzed 109 subjects using data from the Baltimore Longitudinal Study of Aging and found that VOR gain remained stable from ages 26 to 79, after which it significantly declined at a rate of 0.012/year; the prevalence of VOR gain less than 0.8 was 13% in individuals aged ≥80 compared with 2.8% in those aged under 80 (48).…”
Section: The Peripheral Vestibular Systemmentioning
confidence: 99%
“…Notably, this decline was not associated with any symptoms or signs of disequilibrium (47). By contrast, the patients, whose VOR responses were depressed at the start of testing, did not show any significant decline (48). Carol et al analyzed 109 subjects using data from the Baltimore Longitudinal Study of Aging and found that VOR gain remained stable from ages 26 to 79, after which it significantly declined at a rate of 0.012/year; the prevalence of VOR gain less than 0.8 was 13% in individuals aged ≥80 compared with 2.8% in those aged under 80 (48).…”
Section: The Peripheral Vestibular Systemmentioning
confidence: 99%
“…A normal, compensatory VOR gain should equal 1.0. VOR gains less than 0.8, 39 along with compensatory refixation saccades, suggested a loss of peripheral vestibular function. 40 Six individuals from the dementia case group had missing VOR data (two individuals were unable to follow testing instructions, MMSE of 12 and 12, and the equipment was unavailable for testing for the remaining four individuals).…”
Section: Methodsmentioning
confidence: 96%
“…For vHIT testing, a 0.05 difference in VOR gain (standard deviation around 0.1) was chosen as clinically significant. 39 The calculated sample size for the VOR gain analyses was 48 individuals.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously documented an association between vestibular loss and aging in this population (4, 5). In this study, we specifically examined whether VOR gain, compensatory saccade amplitude, and latency were associated with performance on the Short Physical Performance Battery (SPPB).…”
Section: Introductionmentioning
confidence: 88%